Preparation method and application of quinone compound / graphene composite electrode material for 3D printing
The preparation of quinone compound/graphene composite electrodes through 3D printing technology solves the problem of degradation of electrochemical performance of supercapacitors in low temperature environments, and achieves high-quality loads and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411437539.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the electrochemical performance of supercapacitors has significantly decreased in low temperature environments, and inorganic materials have high costs, poor cycle stability and potential environmental risks. The ion transport kinetics in traditional coated thick electrodes are slow and cannot work normally.
The quinone compound/graphene composite electrode was prepared by 3D printing technology, and the graphene composite material modified by quinone compound was prepared by sonication and hydrothermal method, and mixed with conductive agent and adhesive to prepare composite ink, which was manufactured by 3D printing technology. High load three-dimensional electrode structure.
It achieves the maintenance of high-quality load and excellent electrochemical properties under low temperature conditions, including high area specific capacitance, long cycle life and fast reaction kinetics, solving the problems of poor conductivity and stability of quinone compounds.
Smart Images

Figure CN119480469A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of high-mass-loaded organic composite materials and all-organic proton pseudocapacitor negative electrode materials, and specifically to a preparation method and application of 3D printed quinone compound / graphene composite electrode materials. Background Art
[0002] Supercapacitors have been widely used in military, transportation and many other fields due to their high safety, high power density and high ionic conductivity. Electrode materials are an important component closely related to the performance of supercapacitors. Generally speaking, in the process of selecting electrode materials, in addition to evaluating their electrochemical properties, their chemical stability, cost and toxicity should also be considered. Inorganic materials have problems such as high cost, poor cycle stability and potential environmental risks. In comparison, organic materials have great potential as supercapacitor electrode materials due to their high theoretical capacity, flexible molecular structure design, abundant resources, low cost and environmental friendliness. Compared with the metal ion storage mechanism, organic materials and H + The binding mainly depends on hydrogen bonding. This mechanism provides more electron-accommodating sites for the electrode, which can achieve higher capacity. Among many organic materials, quinone compounds can store charges through ionic coordination between cations and carbonyl functional groups, showing high redox reversibility and fast reaction kinetics. When these compounds are composited with carbon-based conductive materials such as graphene or carbon nanotubes (CNTs), the highly electronically conductive carbon substrate helps and alleviates the dissolution of quinones, which can significantly improve the rate performance and cycle stability of the material. Therefore, the development and utilization of organic electrode materials can not only improve the performance of supercapacitors, but also is a key step in achieving sustainable and environmentally friendly energy storage technology.
[0003] All-organic pseudocapacitors utilize reversible redox reactions on the surface / macroporous spaces of organic solids to store charge, which is very different from the ion embedding and de-embedding mechanisms that traditional inorganic electrode materials rely on. This unique charge storage mechanism enables all-organic pseudocapacitors to maintain efficient charge storage at ultra-low temperatures. Currently, there is little research on organic compounds as negative electrodes for proton pseudocapacitors. Although some progress has been made in the field of cryogenic supercapacitors, research related to ultra-low temperature all-organic supercapacitors has just begun, and the mass loading of organic-based electrodes has not yet reached commercial levels (high mass loading >10 mg cm -2 ). To overcome this challenge, direct ink writing (DIW) technology was introduced to prepare high-quality loaded electrodes with 3D structures, improve the utilization of active materials and achieve ideal electrochemical performance. Synergistic optimization of organic molecular design and electrode structure is an effective strategy to construct ultra-low temperature supercapacitors with high energy density and power density.
[0004] How to combine the preparation of quinone compounds / graphene materials with the three-dimensional electrode architecture design of 3D printing, while effectively increasing the mass loading of active substances, maintaining a short ion / electron transmission distance and fast reaction kinetics, and further improving the electrochemical performance of high-mass-loaded all-organic proton pseudocapacitors at low temperatures is a topic of great significance. Summary of the invention
[0005] In view of this, the present invention provides a 3D printed quinone compound / graphene proton pseudocapacitor electrode and a preparation method and application thereof, so as to solve the problems that the electrochemical performance of the inorganic metal oxide materials and the supercapacitors composed thereof in the prior art is significantly reduced under low temperature environment, the conductivity of organic materials is poor, and the ion transfer kinetics in the traditional coated thick electrode is slow and cannot work normally under low temperature conditions.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing a quinone compound / graphene material, comprising:
[0008] Take an appropriate amount of graphene oxide and add it to deionized water. Ultrasonic treatment is carried out at 0-10°C for 1-3 hours to obtain a graphene oxide dispersion. Add quinone compounds to the graphene oxide dispersion and make it fully and evenly dispersed by ultrasonic treatment. Subsequently, the dispersion is transferred to a reactor, and a quinone compound-modified graphene composite material is prepared by a hydrothermal method under high temperature and high pressure conditions. The reaction time is 8-24 hours and the temperature is 180-220°C. The reactants are washed with water and ethanol respectively, frozen and placed in a freeze dryer for 24 hours to obtain a quinone compound / graphene composite aerogel material.
[0009] In a possible implementation, the quinone compound is any one of benzoquinone, naphthoquinone, phenanthrenequinone and anthraquinone, or any one of their derivatives.
[0010] In a possible implementation manner, the mass ratio of the quinone compound to the graphene in the quinone compound / graphene is 1:4-4:1.
[0011] In a second aspect, the present invention provides a method for preparing a quinone compound / graphene composite ink, comprising:
[0012] The quinone compound / graphene composite material, the conductive agent, and the adhesive are added to the solvent in a ratio of 8:1:1. The mixture is ground evenly, and a proper amount of solvent is added after every ten minutes of grinding, and the solvent is evaporated until an ink with a suitable viscosity is obtained.
[0013] In a possible implementation, the adhesive is one of polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene, and the solvent is N-methylpyrrolidone.
[0014] In a third aspect, the present invention provides a method for preparing a 3D printed high-load quinone compound / graphene composite electrode, comprising:
[0015] The obtained ink sample is placed in the syringe of the printer, and printing is performed under pressure, and the printed electrode is freeze-dried for 10 to 12 hours to obtain the final 3D printed quinone compound / graphene electrode;
[0016] In a possible implementation, the needle diameter of the 3D printer is 0.10-0.23 mm; the printed electrode line spacing is 0.2-1 mm, and the nozzle movement speed is 2-5 mm s -1 .
[0017] In a fourth aspect, the present invention provides a 3D printed high-load quinone compound / graphene composite electrode, which is prepared by the above-mentioned preparation method.
[0018] In a fifth aspect, the present invention provides a low-temperature resistant all-organic proton pseudocapacitor of a 3D printed high-load quinone compound / graphene composite electrode, wherein the negative electrode is the 3D printed high-load quinone compound / graphene composite electrode described in the third aspect.
[0019] Beneficial effect: at 100mAcm -2 At a high current density of 25 mg cm -2 7.24F cm under high mass loading -2 High area specific capacitance with a high capacitance retention rate of 61.85% (2mA cm -2 10.14F cm -2 ), and at 100mAcm -2 The capacitance retention rate is as high as 95.6% after 10,000 cycles at a current density of .
[0020] When the 3D printed high-load quinone compound / graphene composite electrode prepared by the present invention is applied to a low-temperature resistant all-organic proton pseudocapacitor, with highly concentrated phosphoric acid as the electrolyte, the composite electrode can provide a long cycle life, high rate performance and exhibit fast reaction kinetics, and a redox reaction can occur on the C=O redox active site of the quinone compound molecule to store ions. Reducing graphene oxide can ensure that the electrode has high electronic conductivity, solving the problem of poor conductivity and stability of quinone compounds. Using the three-dimensional structure carefully designed by 3D printing technology, the high-load quinone compound / graphene composite electrode can maintain rapid ion transmission inside the electrode even under low temperature conditions of -80°C, ensuring that the electrochemical performance will not significantly decrease. Therefore, the 3D printed quinone compound / graphene composite electrode is applied to a low-temperature resistant all-organic proton pseudocapacitor and exhibits excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0022] Figure 1 A schematic diagram of a process for preparing a 3D printed quinone compound / graphene composite electrode provided by the present invention;
[0023] Figure 2 This is a SEM image of a quinone compound / graphene composite material provided by the present invention;
[0024] Figure 3 A Raman graph of a quinone compound / graphene composite material provided by the present invention;
[0025] Figure 4 This is a SEM image of a 3D printed quinone compound / graphene composite electrode provided by the present invention;
[0026] Figure 5 A constant current charge-discharge curve of a 3D printed quinone compound / graphene composite electrode provided by the present invention;
[0027] Figure 6 The present invention provides a low-temperature resistant all-organic proton pseudocapacitor based on a 3D printed quinone compound / graphene composite electrode with a cycling performance at -80°C. DETAILED DESCRIPTION
[0028] In order to better understand the technical solution of the present invention, the present invention is described in detail below with reference to the accompanying drawings.
[0029] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The terms used in the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0031] It should be understood that the term "and / or" used in the present invention is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0032] Inorganic materials have problems such as high cost, poor cycle stability and potential environmental risks. Compared with traditional inorganic pseudocapacitor materials, organic materials and protons (H + ) mainly relies on hydrogen bonding. This mechanism provides more electron-accommodating sites for the electrode, which can achieve higher capacity. Among many organic materials, quinone compounds can store charge through ionic coordination between cations and carbonyl functional groups, showing high redox reversibility and fast reaction kinetics. Although some progress has been made in the field of low-temperature supercapacitors, research related to ultra-low-temperature all-organic supercapacitors has just begun, and the mass loading of organic-based electrodes has not yet reached commercial levels (high mass loading >10 mg cm -2 ). Direct ink writing (DIW) technology is used to prepare high-quality load electrodes with 3D structures, increase the utilization rate of quinone compounds and improve the energy density and power density of proton pseudocapacitors in ultra-low temperature environments.
[0033] Based on this, the present invention provides a quinone compound / graphene composite material, in which the mass ratio of the quinone compound to the graphene oxide material is 1:4 to 4:1.
[0034] When the 3D printed quinone compound / graphene composite electrode is applied to the negative electrode of the proton pseudocapacitor, the quinone compound exhibits excellent electrochemical performance due to its high capacity and fast reaction kinetics. At the same time, the addition of reduced graphene oxide ensures that the material has high electronic conductivity and cycle stability. The three-dimensional porous thick electrode structure manufactured by 3D printing technology can ensure the rapid transmission of ions inside the electrode even at conditions as low as -80°C, so that the electrochemical performance can be maintained without a significant decrease. Therefore, the 3D printed quinone compound / graphene composite electrode exhibits excellent electrochemical performance in the application of low-temperature resistant proton pseudocapacitors.
[0035] Corresponding to the above-mentioned quinone compound / graphene composite material, the present invention also provides a method for preparing a 3D printed quinone compound / graphene composite electrode.
[0036] See also Figure 1 , is a schematic diagram of the process of preparing the 3D printed quinone compound / graphene composite electrode provided by the present invention. Figure 1 As shown, it mainly includes the following steps.
[0037] Step S101: preparing quinone compound / graphene material.
[0038] In a specific implementation, a proper amount of graphene oxide is added to deionized water, and ultrasonic treatment is performed at 0 to 10° C. for 1 to 3 hours to obtain a graphene oxide dispersion. A quinone compound is added to the graphene oxide dispersion, and ultrasonic treatment is performed to fully and evenly disperse the quinone compound.
[0039] In a possible implementation, the quinone compound in the above step is any one of benzoquinone, naphthoquinone, phenanthrenequinone and anthraquinone or any one of their derivatives.
[0040] In one possible implementation, the concentration of the graphene oxide dispersion in the above step is 1 to 4 mg ml -1 For example, 1 mg ml -1 , 2mg ml -1 , 3mg ml -1 , 3.5mg ml -1 , 4mg ml -1 Etc., those skilled in the art can make adaptive selections within this range according to actual needs.
[0041] In one possible implementation, the mass ratio of quinone compound to graphene in the quinone compound / graphene is 1:4-4:1, for example, 1:4, 3:5, 1:1, 1.5:1, 2:1, 4:1, etc., and those skilled in the art can make adaptive selections within this range according to actual needs.
[0042] In a possible implementation, the ultrasonic treatment time in the above step is 1 to 3 hours, for example, 1 hour, 1.5 hours, 3 hours, etc. Those skilled in the art can make an adaptive selection within this range according to actual needs.
[0043] Step S102: preparing quinone compound / graphene material.
[0044] Subsequently, the dispersion was transferred to a reactor, and a quinone compound-modified graphene composite material was prepared by a hydrothermal method under high temperature and high pressure conditions, with a reaction time of 8 to 24 hours and a temperature of 180 to 220°C. The reactants were washed with water and ethanol, respectively, frozen and placed in a freeze dryer for 24 hours to obtain a quinone compound / graphene composite aerogel material.
[0045] In a possible implementation, the reaction temperature in the above steps is 160-220°C, for example, 180°C, 190°C, 200°C, 220°C, etc., and those skilled in the art can make an adaptive selection within this range according to actual needs. It should be noted that if the temperature during the hydrothermal reaction is too low, for example, below 160°C, the conductivity of graphene oxide will be low; if the hydrothermal reaction temperature is too high, for example, above 220°C, the structure of graphene will be destroyed, thereby affecting its performance.
[0046] In a possible implementation, the reaction time in the above steps is 8 to 24 hours, for example, 8 hours, 16 hours, 19 hours, 24 hours, etc. Those skilled in the art can make adaptive selections within this range according to actual needs.
[0047] Step S103: Preparing 3D printed quinone compound / graphene composite electrode
[0048] In a specific implementation, quinone compounds, conductive agents and adhesives can be mixed, ground after adding solvents, and then the solvents can be evaporated until there is no particle feeling and the viscosity is moderate, thereby obtaining viscoelastic ink. The obtained ink sample is placed in the syringe of the printer and printed under pressure to obtain a 3D printed quinone compound / graphene composite electrode.
[0049] In a possible implementation, the binder includes one of polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene, and the solvent is N-methylpyrrolidone. Of course, those skilled in the art can also select other solvents that can dissolve one of polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene according to actual needs, and the embodiments of the present application make specific restrictions on this.
[0050] In a possible implementation, the spacing of the electrode lines 3D printed in the above steps is 0.2 to 1 mm, such as 0.2 mm, 0.66 mm, 0.9 mm, 1 mm, etc. Those skilled in the art can make adaptive selections within this range according to actual needs.
[0051] The present invention also provides a 3D printed low temperature resistant all-organic proton pseudocapacitor, which includes the 3D printed quinone compound / graphene composite electrode prepared in the above embodiment. The 3D printed low temperature resistant all-organic proton pseudocapacitor can achieve high area specific capacitance and high energy density, and has excellent cycle stability even at a temperature of -80°C.
[0052] It can be seen that the method of the present invention is simple, easy to prepare, has high yield, excellent performance, and is suitable for large-scale production.
[0053] For ease of understanding, the technical solution provided by the present invention is described in detail below in conjunction with specific embodiments.
[0054] Embodiment 1:
[0055] The quinone compound was added to the graphene oxide dispersion (2 mg mL -1 ), wherein the quinone compound and graphene oxide are in a mass ratio of 1:1, and are fully and evenly dispersed by ultrasonic treatment. Subsequently, the dispersion is transferred to a reactor, and a quinone compound-modified graphene composite material is prepared by a hydrothermal method under high temperature and high pressure conditions, with a reaction time of 12 hours and a temperature of 220°C. The reactants are washed with water and ethanol respectively, frozen and placed in a freeze dryer for 24 hours to obtain a quinone compound / graphene composite aerogel material.
[0056] See also Figure 2 , is a SEM image of the quinone compound / graphene composite material provided in this embodiment. Figure 2 As shown, the composite material prepared in Example 1 has large pores.
[0057] See also Figure 3 , is the Raman spectrum of the quinone compound / graphene composite material provided in this embodiment. Figure 3 As shown, the ID / IG ratio of the composite material is reduced.
[0058] The composite material, single-walled carbon nanotubes and polyvinylidene fluoride were added to N-methylpyrrolidone in a ratio of 8:1:1 and ground evenly. The solvent was evaporated until the ink had no particle feeling and moderate viscosity. The obtained ink sample was placed in the syringe of the printer and printed under pressure. After freeze drying for more than 24 hours, a 3D printed quinone compound / graphene composite electrode was obtained, wherein the 3D printed electrode line spacing was 0.3 mm.
[0059] See also Figure 4 , is a SEM image of the 3D printed quinone compound / graphene composite electrode provided in this embodiment. Figure 3 As shown, the printed filaments in the 3D printed electrode are continuous and tightly stacked, and no internal collapse occurs at the edges.
[0060] See also Figure 5 , is a constant current charge and discharge diagram of a 3D printed quinone compound / graphene composite electrode provided in this embodiment. In a highly concentrated phosphoric acid electrolyte, the 3D printed composite electrode is charged and discharged at 100 mA cm -2 The high current density still provides 7.24F cm -2 The high area specific capacitance and high capacitance retention rate (2mAcm) of 61.85% -2 10.14F cm -2 ), proving that the 3D printed quinone compound / graphene composite electrode has excellent electrochemical performance as the negative electrode of the proton pseudocapacitor.
[0061] See also Figure 6 , which is a cycling performance diagram of the 3D printed low-temperature resistant all-organic proton pseudocapacitor at –80°C provided in the embodiment of the present application. The 3D printed low-temperature resistant all-organic proton pseudocapacitor was cycled at –80°C for 10,000 times (5 mA cm -2 ) can still achieve stable operation, showing its potential application prospects in meeting the needs of energy storage systems even in extremely low temperatures.
[0062] Embodiment 2:
[0063] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction time is 8 hours.
[0064] Embodiment 3:
[0065] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction time is 24h.
[0066] Embodiment 4:
[0067] The difference between this embodiment and embodiment 1 is that the mass ratio of quinone compound to graphene oxide is 1:4.
[0068] Embodiment 5:
[0069] The difference between this embodiment and embodiment 1 is that the mass ratio of quinone compound to graphene oxide is 4:1.
[0070] Embodiment 6:
[0071] The difference between this embodiment and embodiment 1 is that the concentration of graphene oxide dispersion is 4 mg ml -1 .
[0072] Embodiment 7:
[0073] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction temperature is 200°C.
[0074] Embodiment 8:
[0075] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction temperature is 180°C.
[0076] Embodiment 9:
[0077] The difference between this embodiment and embodiment 1 is that the spacing between the electrode lines of 3D printing is 0.8 mm.
[0078] Embodiment 10:
[0079] The difference between this embodiment and embodiment 1 is that the spacing between the electrode lines of 3D printing is 0.5 mm.
[0080] Comparative Example 1:
[0081] The difference between this embodiment and embodiment 1 is that the graphene oxide is replaced by activated carbon.
[0082] The 3D printed quinone compound / graphene composite electrode prepared in the above embodiment was subjected to the following electrochemical performance test to obtain the test results shown in Table 1.
[0083] (1) Cyclic performance test: The prepared 3D printed quinone compound / graphene composite electrode was tested on the LAND test system at room temperature with a charge and discharge voltage range of -0.5 to 0.4 V and a charge and discharge current of 100 mA cm -2 Constant current charging and discharging at current density;
[0084] (2) Rate performance test: The prepared electrode was tested on a Coster electrochemical workstation at room temperature. The electrode was tested at a current density of 2 mA cm -2 , 5mAcm -2 、8mAcm -2 、10mAcm -2 、50mAcm -2 , 100mA cm -2 Specific capacitance under .
[0085] Table 1:
[0086]
[0087] As shown in Table 1, the 3D printed quinone compound / graphene composite electrode prepared in Example 1 has better area specific capacitance, rate performance and cycle performance.
[0088] The above is only a specific embodiment of the present invention. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. The protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing a 3D printed quinone compound / graphene composite electrode material, characterized in that: The following steps are involved: (1) adding a quinone compound to a graphene oxide dispersion and dispersing the quinone compound fully and evenly; (2) transferring the dispersion into a reaction kettle and preparing a quinone compound-modified graphene composite material by a hydrothermal method; (3) The graphene composite material obtained in step (2) is evenly mixed with a conductive agent and an adhesive to prepare a viscoelastic ink, and printing is performed under a certain pressure to obtain a 3D printed quinone compound / graphene composite electrode.
2. The method according to claim 1, characterized in that The quinone compound is any one of benzoquinone, naphthoquinone, phenanthrenequinone and anthraquinone or any one of their derivatives.
3. The method according to claim 1, characterized in that In step (1), the mass ratio of the quinone compound to graphene oxide is 1:4-4:
1.
4. The method according to claim 1, characterized in that The reaction time of the hydrothermal method is 8 to 24 hours, and the temperature is 180 to 220°C.
5. The method according to claim 1, characterized in that: The adhesive is polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene.
6. The method according to claim 1, characterized in that The steps of preparing viscoelastic ink include: adding a graphene composite material modified by a quinone compound, a conductive agent and an adhesive into a solvent in a ratio of 8:1:1, mixing and grinding evenly, evaporating the solvent until there is no particle feeling and the viscosity is moderate, thereby obtaining printing ink; the solvent is N-methylpyrrolidone.
7. The method according to claim 1, characterized in that The conductive agent is single-walled carbon nanotube or multi-walled carbon nanotube.
8. The method according to claim 1, characterized in that: The preparation of 3D printed quinone compound / graphene composite electrode includes the following steps: First, the three-dimensional model of the target pattern is imported into the control software of the 3D printing system and automatically sliced. The material tube filled with ink is installed on the 3D printer, and the electrode is constructed layer by layer according to the pre-designed printing program. After printing, the formed structure is freeze-dried to finally obtain the 3D printed quinone compound / graphene composite electrode. The needle diameter of the 3D printer is 0.10-0.23 mm. The printed electrode line spacing is 0.2-1 mm, and the nozzle movement speed is 2-5 mm s -1 .
9. A 3D printed quinone compound / graphene composite electrode, characterized in that: The product is prepared by the preparation method described in any one of claims 1 to 8.
10. A 3D printed low temperature resistant all-organic proton pseudocapacitor, characterized in that: The negative electrode is the 3D printed high-load quinone compound / graphene composite electrode as described in claim 9.
Citation Information
Patent Citations
Graphene / quinones composite material, preparation method and secondary cell
CN104183824A
Quinone compound-graphene composite material and preparation method thereof as well as flexible lithium secondary battery
CN104752727A
Organic positive electrode material, preparation method, positive electrode plate, lithium ion capacitor and lithium metal battery
CN116454278A
Preparation method and application of 3D printing polydiaminonaphthalene / graphene composite electrode
CN118016451A
Structural supercapacitor
EP3392894A2